2016
DOI: 10.1111/phen.12158
|View full text |Cite
|
Sign up to set email alerts
|

On the relevance of using laboratory selection to study the adaptive value of circadian clocks

Abstract: Abstract. The phrase 'as sure as night comes after day' highlights the most conspicuous phenomenon on earth (i.e. the daily cycling of geophysical factors). It is hypothesized that life-forms on earth have evolved timekeeping mechanisms (circadian clocks) as adaptations to cope with such cyclic variations in their environment and, to test this hypothesis, diverse strategies have been employed. In this review, these different approaches, including comparative, clinal, ecology and/or trait manipulation and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The adaptive value of circadian clocks for fitness has been demonstrated by diverse strategies that have been nicely reviewed by Vaze and Sharma (2013), Abhilash and Sharma (2016), and Nikhil and Sharma (2017). One of many possible strategies is to investigate whether a trait confers higher adaptive advantage in the context of species competition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptive value of circadian clocks for fitness has been demonstrated by diverse strategies that have been nicely reviewed by Vaze and Sharma (2013), Abhilash and Sharma (2016), and Nikhil and Sharma (2017). One of many possible strategies is to investigate whether a trait confers higher adaptive advantage in the context of species competition.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the mentioned studies have certain limitations (see Abhilash and Sharma, 2016). Some focused on a single readout of fitness (e.g., lifespan) and did not regard others (e.g., fecundity) that may have compensatory effects on overall fitness (see Sheeba et al, 2000 for an example).…”
Section: Introductionmentioning
confidence: 99%
“…While studies on circadian rhythms under naturalistic regimes have been carried out previously, most have not been explicitly designed to provide evolutionary insights. Our study describes an experimental system tailored explicitly for testing such hypotheses (Abhilash and Sharma, 2016). We found that rearing D. melanogaster populations under semi-natural conditions resulted in phenotypic change compared to the ancestral controls.…”
Section: Discussionmentioning
confidence: 99%
“…Most insects exhibit daily rhythms, such as sleep–wake cycles and nocturnal/diurnal activity, in their behavior. Appropriate behavior at the right time of the day increases the efficiency of daily life and improves fitness (Vaze and Sharma 2013 ; Abhilash and Sharma 2016 ; Horn et al 2019 ). Circadian behavioral rhythms (circa = about and dies = day from Latin terms) are controlled by a circadian clock that generates approximately 24 h rhythms in a self-sustaining manner.…”
Section: Introductionmentioning
confidence: 99%